Fuzzy SWOT-DEA Approach for Selecting Electrical Component Vendors in Offshore Structure Projects - Mohammad Iqbal Putra Azhari; Udisubakti Ciptomulyono (Institute of Research and Community Outreach, Petra Christian University, 2026)
This study analyzes the selection of electrical component vendors in an offshore structure EPC project during the detailed engineering design (DED) and procurement stages, vendor evaluation is critical to ensuring project quality and schedule compliance. A multi-criteria decision-making approach combining the Fuzzy SWOT and data envelopment analysis (DEA) methods was employed to assess 15 electrical cable vendors bidding for Project X in an EPC company based in Jakarta. The Fuzzy SWOT method was used to qualitatively assess each vendor based on predetermined selection criteria, while DEA measured their relative efficiency quantitatively. The analysis identified two vendors, PT. STD and PT. KBL, as the most efficient with an efficiency score of 1. This integrated approach offers a robust, objective framework for vendor selection, supporting efficient procurement decisions that align with project requirements and reduce the risk of delays and quality issues in the construction phase.